MOLECULAR DETECTION OF SARS-COV-2 BY REAL-TIME RT-PCR AND THE ASSOCIATION OF IMMUNOLOGICAL MARKERS (IL-4 AND IL-6) WITH COVID-19 PATIENT GROUPS - Tuamah, Mustafa Raheem; Jasim, Zahra Mohammed (PT. Antis International Publisher, 2025)
Objective: Coronaviruses (CoVs) refer to one of the RNA virus infections that can appear as diseases affecting humans. They're enveloped viruses with massive single-strand positive-sense RNA genomes that can infect humans, animals, birds, bats, mice, and a number of other wild creatures’ respiratory, gastrointestinal, hepatic, and central nervous systems. Method: Viral samples were collected from 90 patients through nasopharyngeal swabs. COVID-19 and non-COVID-19 serum patients’ cytokines were identified by ELISA, while SARS-CoV-2 IL-4 and IL-6 were recognized using the chemiluminescence method. Result: The S gene is generally present in the early stages of infection, with only a few extended periods of contamination, whereas the E gene appears in the later stages of disease—one to several weeks after the onset of infection—while the N gene appears to a lesser extent. With 90% amino acid homology and fewer modifications over time, the N gene is more regulated and stable. The (S and E gene) heterozygote shows a higher rate than the others. Novelty: This study highlights distinct gene expression patterns of SARS-CoV-2 during different stages of infection, revealing that the N gene exhibits greater stability and regulatory consistency, which could be significant for diagnostic and molecular surveillance applications.